LncRNAs and PRC2: Coupled Partners in Embryonic Stem Cells - Alessandro Fiorenzano; Emilia Pascale; Eduardo Jorge Patriarca; Gabriella Minchiotti; Annalisa Fico (Epigenomes, 2019)
The power of embryonic stem cells (ESCs) lies in their ability to self-renew and differentiate. Behind these two unique capabilities is a fine-tuned molecular network that shapes the genetic, epigenetic, and epitranscriptomic ESC plasticity. Although RNA has been shown to be functionally important in only a small minority of long non-coding RNA genes, a growing body of evidence has highlighted the pivotal and intricate role of lncRNAs in chromatin remodeling. Due to their multifaceted nature, lncRNAs interact with DNA, RNA, and proteins, and are emerging as new modulators of extensive gene expression programs through their participation in ESC-specific regulatory circuitries. Here, we review the tight cooperation between lncRNAs and Polycomb repressive complex 2 (PRC2), which is intimately involved in determining and maintaining the ESC epigenetic landscape. The lncRNA-PRC2 partnership is fundamental in securing the fully pluripotent state of ESCs, which must be primed to differentiate properly. We also reflect on the advantages brought to this field of research by the advent of single-cell analysis.